Effects of biological sex and pregnancy in experimental autoimmune encephalomyelitis: It’s complicated - McCombe, Pamela A.; Greer, Judith M. (Frontiers in Immunology, 2022)
Experimental autoimmune encephalomyelitis (EAE) can be induced in many animal strains by inoculation with central nervous system antigens and adjuvant or by the passive transfer of lymphocytes reactive with these antigens and is widely used as an animal model for multiple sclerosis (MS). There are reports that female sex and pregnancy affect EAE. Here we review the effects of biological sex and the effects of pregnancy on the clinical features (including disease susceptibility) and pathophysiology of EAE. We also review reports of the possible mechanisms underlying these differences. These include sex-related differences in the immune system and in the central nervous system, the effects of hormones and the sex chromosomes and molecules unique to pregnancy. We also review sex differences in the response to factors that can modify the course of EAE. Our conclusion is that the effects of biological sex in EAE vary amongst animal models and should not be widely extrapolated. In EAE, it is therefore essential that studies looking at the effects of biological sex or pregnancy give full information about the model that is used (i.e. animal strain, sex, the inducing antigen, timing of EAE induction in relation to pregnancy, etc.). In addition, it would be preferable if more than one EAE model were used, to show if any observed effects are generalizable. This is clearly a field that requires further work. However, understanding of the mechanisms of sex differences could lead to greater understanding of EAE, and suggest possible therapies for MS.